Rodents in the arena: a critical evaluation of methods measuring personality traits. Issue 1 (2nd January 2019) - Mazzamuto, Maria Vittoria; Cremonesi, Giacomo; Santicchia, Francesca; Preatoni, Damiano; Martinoli, Adriano; Wauters, Lucas A.
Abstract : The Open Field Test (OFT) and Mirror Image Stimulation (MIS) are used to measure behaviours related to an individual's personality. These tests, carried out in a same novel arena, have been used for different taxa, but only a few papers underline the importance of method validation. Here we investigate how Eurasian red squirrels ( Sciurus vulgaris ) and Eastern grey squirrels ( Sciurus carolinensis ) behave during OFT and MIS. Next, we compare the performance between three analytical methods: the Principal Component Analysis (PCA), the Factor Analysis (FA) and an expert-based (EB) method. The EB approach classifies behaviours in groups relating on researchers' knowledge and returns personality-trait values for each individual facilitating comparisons over studies and/or with new datasets. The comparison between the three methods gave similar results and high repeatabilities in some expert-based personality traits as well as PCA components and FA factors, showing that all three methods were valid to measure activity using OFT (both species) and sociability using MIS (grey squirrel). Repeatabilities of the other traits were less strong. Proportion of time spent in different behaviours did not differ with test duration, since shorter tests yielded valid measures of individual differences in personality. Shorter tests reduce operator time in the field, and are likely to reduce stress and arena-habituation of the animals. Test sequence affected the outcome of OFT: squirrels tested for the first time were more active than squirrels tested a second time. For the two squirrel species investigated, we recommend an OFT of 4 min and a MIS test of three and suggest to test an individual no more than 2 times per season with at least 2 months between repetitions.